Stereotactic radiosurgery in the treatment of essential tremor – a systematic review - Bilski, Mateusz; Szklener, Katarzyna; Szklener, Sebastian; Rudzińska, Anna; Kluz, Natalia; Klas, Jakub; Rodzajewska, Anna; Kuryło, Weronika; Korga, Mateusz; Baranowska, Izabela; Mańdziuk, Sławomir (Frontiers in Neurology, 2024)
Introduction Essential tremor (ET) is the most common movement disorder in adults, with an estimated incidence of up to 1% of the population and 5% of people older than 65 years of age. ET is manifested primarily by bilateral postural and kinetic tremor of the upper limbs with or without neurological symptoms and cognitive deficits. ET disrupts daily tasks and significantly lowers quality of life. Currently available medications alone are often insufficient to control severe symptoms. Several surgical treatment options are available, including stereotactic radiosurgery (SRS)—a minimally invasive treatment option aimed at relieving and controlling tremors. Methods We conducted a systematic review of the scientific literature on the use of SRS in the treatment of ET using PubMed, Scopus, Web of Science, Cochrane, ScienceDirect, and ClinicalTrials.gov registry and adhered to the PRISMA guidelines. Results The results obtained confirm the high efficacy and safety of the SRS procedure in treating drug-resistant intention tremor. The study results present high response rate reaching 80% and achievement of manual task improvement, lessening of the tremor and increase in the quality of life of the majority of the operated patients. The method also stands out for its favorable balance between efficiency and cost. Disscusion Stereotactic radiosurgery is a favourable, safe, efficient and cost-effective method in treatment of the essential tremor. Ongoing research is crucial to refine patient selection criteria for this procedure and further improve the effectiveness of the technique.